2015
DOI: 10.1021/jm500829b
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Intestinal Targeted TGR5 Agonists for the Treatment of Type 2 Diabetes

Abstract: Activation of TGR5 stimulates intestinal glucagon-like peptide-1 (GLP-1) release, but activation of the receptors in gallbladder and heart has been shown to cause severe on-target side effects. A series of low-absorbed TGR5 agonists was prepared by modifying compound 2 with polar functional groups to limit systemic exposure and specifically activate TGR5 in the intestine. Compound 15c, with a molecular weight of 1401, a PSA value of 223 Å(2), and low permeability on Caco-2 cells, exhibited satisfactory potency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 33 publications
2
59
0
Order By: Relevance
“…MN6 demonstrated a high permeability in Caco-2 cells in our previous report (P app =6.75×10 -6 cm/s) [20] . In the current study, Caco-2 cells were used to evaluate the permeability of OL3 in vitro.…”
Section: Ol3 Demonstrated Low Permeability In Caco-2 Cellssupporting
confidence: 48%
See 1 more Smart Citation
“…MN6 demonstrated a high permeability in Caco-2 cells in our previous report (P app =6.75×10 -6 cm/s) [20] . In the current study, Caco-2 cells were used to evaluate the permeability of OL3 in vitro.…”
Section: Ol3 Demonstrated Low Permeability In Caco-2 Cellssupporting
confidence: 48%
“…Among them, MN6 ([4-(2, 5-dichlorophenoxy) pyridin-3-yl]-(4-cyclopropyl-3,4-dihydro-2H-quinoxalin-l-yl) methanone (described as compound 22g in reference 19) is one of the most potent molecules with an EC 50 of 1.5 nmol/L and 18 nmol/L on human and mouse TGR5 (h/mTGR5), respectively, and without activation effects on FXR [19] . Oral administration of MN6 (described as compound 2 in reference 20) also increased the gallbladder volume in mice [20] . Compounds with a large molecular weight (MW) and a high topological polar surface area (tPSA) exhibit low membrane permeability and decreased intestinal absorption [21] .…”
Section: Original Articlementioning
confidence: 97%
“…It could be noted that various substitutions at position 4 of compound 30c were well tolerated, such as bromo (30n), methyl (31c) and hydroxyl (31d) substituents, which suggested that other groups might also be well tolerated. 32) As a general rule, the 2-methylthiazole scaffold successfully maintained excellent in vitro potency.…”
Section: Resultsmentioning
confidence: 93%
“…Therefore, TGR5 has emerged as an attractive drug target for metabolic diseases and various TGR5 agonists have been developed [5,23,24,[36][37][38][39][40] .…”
Section: Tgr5 In Liver Damage: Insights From Mice Treated With Varioumentioning
confidence: 99%
“…Furthermore, due to the extremely high expression of TGR5 in gallbladder tissue as compared to other tissues such as the intestine, effects on gallbladder filling were observed with lower concentrations of a TGR5 agonist (compound 18) as effects on GLP-1 secretion [5] . These findings may limit the use of systemically available TGR5 agonists for the treatment of metabolic disease, however, may be overcome by molecules with low systemic bioavailability, which specifically target intestinal TGR5 [5,36] .…”
Section: Tgr5 In Liver Damage: Insights From Mice Treated With Varioumentioning
confidence: 99%